Quantitative characterization of microstructure of pure copper processed by ECAP - Šedivý, Ondřej (Image analysis and stereology, 2013)
Orientation imaging microscopy (OIM) allows to measure crystallic orientations at the surface of the material. Digitalized data representing the orientations are processed to recognize the grain structure and they are visualized in crystal orientation maps. Analysis of the data firstly consists in recognition of grain boundaries followed by identification of grains themselves. Knowing the grain morphology it is possible to characterize the homogeneity of the structure and estimate structural parameters related to the physical properties of the material. The paper describes methods of imaging and quantitative characterization of the grain boundary structure in metals based on data from electron backscattered diffraction (EBSD).
Keywords: electron backscatter diffraction; stereologija; equal-channel angular pressing; metalografija; random marked sets; baker; EBSD; second-order analysis; uklon povratno sipanih elektronov; statistična analiza